Evaluation of Hospital Outcomes Among Very Low Birth Weight Babies in a Community-Level Medical College Hospital (The Journal of Ad-din Women's Medical College, 2025)
Introduction: Very low birth weight (VLBW) babies are at increased risk from a wide range of hazards resulting from immaturity of structure and functions of many organs, which may cause death or permanent damage. Objective: The objective of this study was to evaluate immediate outcomes in VLBW babies. Materials and Methods: This hospital-based prospective cohort study was conducted in the Department of Paediatrics, Kumudini Women’s Medical College and Hospital, Mirzapur, Tangail from August 2008 to July 2009. At enrollment VLBW babies (birth weight